ASPEK WACANA DALAM CERITA ANAK BERBAHASA INGGRIS - Nur Fatimah (LITERA, 2009)
This study aims to describe cohesive devices, discourse making elements, and children’s characters in children’s English stories. This study employed the microstructural and macrostructural discourse analysis. The data source was http:// www.britishcouncil.org/ kids/stories. The findings are as follows. First, the Englishstories under study use cohesive devices such as references, substitutions, ellipses, and conjunctions. Second, the stories present positive descriptions of children, showing that they can get along well, are pleasant, are altruistic, are close to families and friends, have dynamic and creative activities, and can solve problems.